Effects of running on human Achilles tendon length-tension properties in the free and gastrocnemius components - Lichtwark, G. A.; Cresswell, A. G.; Newsham-West, R. J. (The Journal of Experimental Biology, 2013)
The elastic properties of the human Achilles tendon are important for locomotion; however, in vitro tests suggest that repeated cyclic contractions lead to tendon fatigue - an increase in length in response to stress applied. In vivo experiments have not, however, demonstrated mechanical fatigue in the Achilles tendon, possibly due to the limitations of using two-dimensional ultrasound imaging to assess tendon strain. This study used freehand three-dimensional ultrasound (3DUS) to determine whether the free Achilles tendon (calcaneus to soleus) or the gastrocnemius tendon (calcaneus to gastrocnemius) demonstrated tendon fatigue after running exercise. Participants (N=9) underwent 3DUS scans of the Achilles tendon during isometric contractions at four ankle torque levels (passive, and 14, 42 and 70 N m) before and after a 5 km run at a self-selected pace (10-14 km h-1). Running had a significant main effect on the length of the free Achilles tendon (P<0.01) with a small increase in length across the torque range. However, the mean lengthening effect was small (<1%) and was not accompanied by a change in free tendon stiffness. There was no significant change in the length of the gastrocnemius tendon or the free tendon cross-sectional area. While the free tendon was shown to lengthen, the lack of change in stiffness suggests the tendon exhibited mechanical creep rather than fatigue. These effects were much smaller than those predicted from in vitro experiments, possibly due to the different loading profile encountered and the ability of the tendon to repair in vivo.